WoM Role on The Tourist Attraction Image and Re-visit Intention - Unggul Saragih, Darwin Raja; Said, Farid (Jurnal Indonesia Sosial Sains, 2024)
As an educational tourist attraction, the Zoology Museum can give visitors memorable experiences and help managers evaluate and improve their operations. This study aims to analyze the direct impact of word-of-mouth into tourist attraction image and re-visit intention. This study used the purposive sampling method and quantitative approach to evaluate reflective indicators and the relationship between variables. Google Forms and surveys were used to get data from a sample of 258 respondents and 30 were first tested for validity and reliability to ensure the analysis was continued. Data processing used SEM PLS 3.0 software. The result indicates that word-of-mouth significantly increases re-visit intention. The results show that tourist attraction images significantly increase re-visit intention, including word-of-mouth as a mediator. Word-of-mouth is pivotal in the tourism industry, and this study underscores its merits for visitors and management. By incorporating sustainable practices into the marketing process, the management of the Zoology Museum can distinguish its services and products and cultivate a robust brand identity. The findings of this study indicate a positive and substantial impact of the tourist attraction's image on re-visit intention. At the same time, word-of-mouth also significantly influences re-visit intention